Non-linear Optical Responses of Low-Density Lipoprotein are Associated with Intima-Media Thickness of Carotid Artery in Athletes - Fonseca, Henrique Andrade R.; Bittencourt, Célia R.; Fonseca, Francisco A.; Monteiro, Andrea M.; Santos, Priscila R.; Camargo, Luciano; Costa, Luiz A. R.; Murad, Alexandre; Gidlund, Magnus; Figueiredo-Neto, Antonio M.; Izar, Maria Cristina O. (Cell biochemistry and biophysics, 2016)
We investigated the association between the degree of oxidative modification of LDL particles by non-linear optical response of LDL (Z-scan technique) and the presence of subclinical atherosclerosis in different segments of the carotid artery. We recruited high-intensity athlete runners ( n = 44) and controls ( n = 51) to participate in the study. The carotid intima-media thickness (cIMT), interleukin 10 (IL-10), TNF-alpha, and the non-linear optical responses of LDL particle (Z-scan) were assessed. In athletes, the mean cIMT differed between genders, with higher values observed in female athletes compared to male athletes ( P < 0.05). Higher mean values for cIMT were seen in the right carotid arteries of female athletes as compared to female controls ( P < 0.05). Higher levels of TNF-alpha and IL-10 were found in athletes ( P < 0.05). Yet, Δ Γ pv (transmittance curve) of Z-scan in athletes was higher than in the non-athletes, indicating less oxidation in LDL particles of athletes ( P < 0.05). There was an inverse association between the Δ Γ pv and cIMT in the right internal carotid segments ( β = −0.163, P < 0.05) in all subjects, and between the VO 2max and the mean cIMT ( β = −0.003, P < 0.05) in male subjects. The present study shows that the Z-scan technique enabled to detect less oxidative modifications in LDL particles from athletes. This effect was associated with cIMT in a gender-dependent mode.